CD4+ T cells from patients with primary sclerosing cholangitis exhibit reduced apoptosis and down‐regulation of proapoptotic Bim in peripheral blood. Issue 2 (14th September 2016) - Schoknecht, Tanja; Schwinge, Dorothee; Stein, Stephanie; Weiler‐Normann, Christina; Sebode, Marcial; Mucha, Sören; Otto, Benjamin; Ellinghaus, Eva; Stahl, Felix; Franke, Andre; Lohse, Ansgar W.; Herkel, Johannes; et al.
Abstract : The pathogenesis of the progressive liver disease, primary sclerosing cholangitis (PSC), remains largely elusive. The strong genetic association with HLA loci suggests that T cell–dependent, adaptive immune reactions could contribute to disease pathogenesis. Recent studies have indicated that PSC is also associated with polymorphisms in the locus encoding for proapoptotic Bim ( BCL2L11 ). Bim is crucial for the maintenance of immunologic tolerance through induction of apoptosis in activated T cells. Of interest with regard to PSC is the finding that BCL2L11 ‐deficient mice develop periductular infiltrates. We, therefore, investigated, whether defective apoptosis of T cells might contribute to the phenotype of PSC. Thus, we induced apoptosis of T cells from patients with PSC and controls by repeated T cell receptor (TCR) stimulation or cytokine withdrawal. We found that CD4 + T cells, but not CD8 + T cells, from patients with PSC exhibited significantly reduced apoptosis in response to both, TCR restimulation or cytokine withdrawal. This increased apoptosis resistance was associated with significantly reduced up‐regulation of proapoptotic Bim in T cells from patients with PSC. However, T cell apoptosis did not seem to be influenced by the previously described BCL2L11 polymorphisms. Reduced CD4 + T cell apoptosis in patients with PSC was not due to reduced cell activation, as indicated by a similar surface expression of the activation markers CD69, CD25, and CD28 in T cells from patients and controls. Thus, decreased apoptosis of activated CD4 + T cells may be part of the immune dysregulation observed in patients with PSC.